Facilely Tuning the First-Shell Coordination Microenvironment in Iron Single-Atom for Fenton-like Chemistry toward Highly Efficient Wastewater Purification - Zelin Wu; Bingkun Huang; Xinhao Wang; He, Chuan-Shu; Yang Liu; Du, Ye; Liu, Wen; Zhaokun Xiong; Bo Lai (Environmental Science & Technology, 2023)
Precisely identifying the atomic structures in single-atom sites and establishing authentic structure–activity relationships for single-atom catalyst (SAC) coordination are significant challenges. Here, theoretical calculations first predicted the underlying catalytic activity of Fe–NxC4–x sites with diverse first-shell coordination environments. Substituting N with C to coordinate with the central Fe atom induces an inferior Fenton-like catalytic efficiency. Then, Fe-SACs carrying three configurations (Fe–N2C2, Fe–N3C1, and Fe–N4) fabricate facilely and demonstrate that optimized coordination environments of Fe–NxC4–x significantly promote the Fenton-like catalytic activity. Specifically, the reaction rate constant increases from 0.064 to 0.318 min–1 as the coordination number of Fe–N increases from 2 to 4, slightly influencing the nonradical reaction mechanism dominated by 1O2. In-depth theoretical calculations unveil that the modulated coordination environments of Fe-SACs from Fe–N2C2 to Fe–N4 optimize the d-band electronic structures and regulate the binding strength of peroxymonosulfate on Fe–NxC4–x sites, resulting in a reduced energy barrier and enhanced Fenton-like catalytic activity. The catalytic stability and the actual hospital sewage treatment capacity also showed strong coordination dependency. This strategy of local coordination engineering offers a vivid example of modulating SACs with well-regulated coordination environments, ultimately maximizing their catalytic efficiency.